As memórias do passado e do futuro na constituição do sujeito: uma análise de enunciados de imigrantes italianos no Brasil - Montessi, Mauri Siqueira (2008)
In this research, it was intended to show that Memories of Past and the Memories of Future, as created by Bakhtin, shared collectively by individuals in a social organization that produces self-images of those individuals in interaction. To defend that point of view, firstly it was necessary to define the original images of the individuals through their speech, and then to analyze how those memories have participated in that construction. First of all the corpus to analyze has been chosen: three books written by Italian immigrants that moved to Brazil when they were young and lived all their lives here. The construction of the images was considered like construction of identities. That process was studied as an otherness, i.e., identities are built from others. In the analysis, it was observed that the relationship between Memories of the Past and Memories of the Future, the latter project a future of peace, tranquility etc, and the former bring to present a past of pain, sorrow, poverty etc, created images of lawful individuals, workers, happy, persistent etc; and there was a direct relationship between those memories and those identities, i.e., one producing the other